Toward a sensory approach to Tactical Urbanism - Di Croce, Nicola; Guastavino, Catherine (City (London, England), 2025)
In the last decades, Tactical Urbanism has emerged as a bottom-up approach addressing the state of abandonment or underuse of problematic urban areas through ephemeral, temporary interventions aiming to trigger positive and long-term benefits to derelict areas. While Tactical Urbanism interventions usually have a strong visual component, in this article we focus on the possibilities offered by sound-based tactical interventions informed by participatory design processes engaging residents and local actors of neighborhoods undergoing transformation. Highlighting the role of city users' sonic experience in the everyday environment, we illustrate how a sound-based approach to Tactical urbanism can help exploring alternative means of questioning neoliberal urbanism, especially by supporting the livability of residents and city users beyond the primary drive toward visitors' attractiveness. To support our argument, we present and discuss the outcomes of a two-year project in the Montreal's Quartier des Spectacles, a neighborhood undergoing drastic social, spatial, and economic transformations. Here, after a first ethnographic and sonic investigation, we organized two participatory workshops focused on the sonic experience of the neighborhood, which culminated in the realization of a sound installation.